Film for removing electrode material and method for removing electrode material
Patent Information
- Application Number
- JP2025059770
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166673000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to recycling of electrode materials from spent secondary batteries, and more specifically, relates to a peeling film and a peeling method for peeling an active material layer from a current collector constituting the electrode material.
Background Art
[0002] In recent years, recycling of waste lithium-ion batteries has been attracting attention. Among them, for waste lithium-ion batteries containing rare metals such as NCA, recycling processes that burn the waste batteries themselves and extract rare metals from the remaining metals are being studied. (For example, refer to Patent Document 1)
[0003] However, for lithium iron phosphate that does not contain rare metals, such recycling processes are not economically viable. Conventionally, in the recycling of spent lithium iron phosphate (hereinafter referred to as "LFP") batteries, lithium contained in LFP is extracted and recycled, but other iron sources and phosphorus sources have been discarded. However, under the current circumstances, in the technology of taking out positive electrodes from spent LFP batteries and separating and regenerating the positive electrode materials on the surface of the positive electrodes, although there are positive electrode material separation methods such as the electric pulse method, there are various problems such as large-scale equipment, low processing capacity, and the aluminum foil as the current collector being destroyed during the separation process and mixed into the recovered positive electrode active material.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of Invention
Problem to be Solved by the Invention
[0005] The present invention has been made in view of the above problems, and provides an electrode material peeling film and an electrode material peeling method for efficiently peeling and recovering electrode material from the electrodes of used secondary batteries. [Means for solving the problem]
[0006] In other words, according to one aspect of the present invention for solving the above problems, the first aspect of the present invention is an electrode material release film comprising a stimulus-curing type easily peelable adhesive layer on the surface of a base film and a hot-melt type adhesive layer provided on the stimulus-curing type easily peelable adhesive layer.
[0007] A second aspect of the present invention is a film for peeling off electrode materials in which the stimulus-curing type easily peelable adhesive layer in the first aspect is an ultraviolet-curing type easily peelable adhesive layer.
[0008] A third aspect of the present invention is an electrode material release film having a dry film thickness of 0.5 μm or more and 10 μm or less for the hot-melt adhesive layer in the first aspect.
[0009] A fourth aspect of the present invention is, in the second aspect, a film for releasing electrode materials having an ultraviolet irradiation transmittance of 85% or more at a wavelength of 365 nm.
[0010] A fifth aspect of the present invention is an electrode material release film in which the softening point of the hot-melt adhesive layer in the first aspect is 80°C or higher and 155°C or lower.
[0011] A sixth aspect of the present invention is an electrode material release film in which the thickness of the base film in the first aspect is 10 μm or more and 300 μm or less.
[0012] A seventh aspect of the present invention is an electrode material release film in which the electrode material in the first aspect is the positive electrode material.
[0013] An eighth aspect of the present invention is an electrode material release film in which the electrode material in the first aspect is the negative electrode material.
[0014] The ninth aspect of the present invention is a method for peeling an electrode material using an electrode material peeling film according to the first to eighth aspects, A step of bonding the hot-melt adhesive layer to the surface of the active material layer of an electrode material comprising a metal layer and an active material layer, A step of heating the hot-melt adhesive layer to bond the active material layer and the hot-melt adhesive layer, A step of peeling the active material layer from the metal layer using a transfer means and transferring the active material layer to an electrode material peeling film, A step of stimulating the electrode material peeling film to cure the stimulation-curing type easily peelable adhesive layer, The method for peeling off electrode material is characterized by comprising a step of separating the active material layer from the electrode material peeling film using a separation means. [Effects of the Invention]
[0015] According to the present invention, it is possible to provide an electrode material peeling film and an electrode material peeling method for efficiently peeling and recovering electrode material from the electrodes of used secondary batteries. [Brief explanation of the drawing]
[0016] [Figure 1] This is a cross-sectional diagram of the electrode material. [Figure 2] This is a cross-sectional diagram of the electrode material release film according to the present invention. [Figure 3] This is an explanatory diagram of an electrode material peeling apparatus according to the present invention. [Modes for carrying out the invention]
[0017] An example of the electrode material of the present invention is shown in Figure 1. In Figure 1, 1 is the electrode material, which has a configuration in which an active material layer 12 is provided on both sides or one side of a metal layer 11. Here, the metal layer 11 acts as a current collector in a lithium-ion battery, and aluminum foil or copper foil is commonly used. Here, the electrode materials in the present specification include not only positive electrode materials that use lithium nickel cobalt manganese composite oxide or lithium iron phosphate as the positive electrode active material and consist of a binder, a conductive aid, etc., but also negative electrode materials that consist of a negative electrode active material (e.g., carbon), a binder, a conductive aid, etc. That is, not only the method for peeling a positive electrode material but also the method for peeling a negative electrode material are included within the scope of the present invention. More specifically, as described in the following examples, the present invention is not limited to the case where the metal layer in the positive electrode material is an aluminum foil and the active material thereof is lithium iron phosphate, and the metal layer in the negative electrode material layer may be a copper foil and the active material thereof may be made of carbon.
[0018] An example of the film 2 for peeling an electrode material according to the present invention is shown in Figure 2. The film 2 for peeling an electrode material is a film having both adhesiveness and curability upon stimulation, and as one configuration thereof, it is a film provided with a stimulus-curable easily peelable adhesive layer 20 having both stimulus curability and adhesiveness on a base film 21. An integrated product of the base film 21 and the stimulus-curable easily peelable adhesive layer 20 can also be used.
[0019] As the stimulation source for the stimulus-curable easily peelable adhesive layer 20, radiation such as ultraviolet rays, heat (temperature), or pressure is used, but from the viewpoint of ease of handling, it is preferable to use an ultraviolet-curable easily peelable adhesive layer. Further, a hot-melt adhesive layer 22 is formed on the surface of the stimulus-curable easily peelable adhesive layer 20 by coating to form the film 2 for peeling an electrode material. As the base film 21, a film formed of PET or an acrylic resin, or a film formed of paper, synthetic fibers, or the like can be used, but it is preferable to use a PET film from the viewpoint of ultraviolet transmittance.
[0020] The ultraviolet-curable easily peelable adhesive layer has high adhesion to various substances due to the adhesive layer before ultraviolet irradiation, but is cured to lose adhesiveness upon ultraviolet irradiation, and can be easily peeled off.
[0021] Next, the peeling method according to the present invention will be explained using the explanatory diagram shown in Figure 3. In Figure 3, reference numeral 30 denotes a conceptual diagram of the peeling device used, 31 is a heating roll, 32 is a transfer roll, 33 is a separation roll, 34 is a conveying roll, 35 is a winding roll, 36 is a scraper, and 37 is a recovery container.
[0022] The peeling method according to the present invention first involves applying a hot-melt adhesive to a stimulus-curing, easily peelable adhesive layer 20 on a base film 21 to form a hot-melt adhesive layer 22. The film having this hot-melt adhesive layer on its surface is called the electrode material peeling film 2. In this case, an ultraviolet-curing, easily peelable adhesive layer was used as the stimulus-curing, easily peelable adhesive layer 20.
[0023] The electrode material peeling film 2 is conveyed by the conveying roll 34 and the winding roll 35 so as to be opposite the surface of the electrode material 1.
[0024] The hot-melt adhesive layer of the electrode material release film 2 is bonded to the active material layer 12 on the surface of the electrode material 1, and press pressure is applied while heating with a heating roll 31. This causes the active material layer 12 and the hot-melt adhesive layer 22 on the surface of the electrode material release film 2 to bond together.
[0025] In one embodiment of the present invention, the active material layer 12 adhered to the electrode material release film 2 is peeled off from the metal layer (aluminum foil) 11, starting from the contact area with the transfer roll 32. In other words, the active material layer 12 is transferred from the electrode material 1 to the electrode material release film 2, starting from the contact area with the transfer roll 32. Subsequently, by irradiating the electrode material release film 2, onto which the active material layer 12 has been transferred, with ultraviolet light, the stimulus-curing type easily peelable adhesive layer 20 is cured, and its tackiness is reduced.
[0026] The electrode material release film 2, onto which the active material layer 12 has been transferred, is transported by a transport roll 34 and a winding roll 35. Then, the active material layer 12, along with the hot melt adhesive layer 22, is separated from the electrode material release film 2 by a separation roll 33 and a scraper 36. The separated active material layer 12 is collected in a recovery container 37. In the case of a configuration in which an active material layer 12 is provided on both sides of a metal layer (aluminum foil) 11, as shown in the explanatory diagram in Figure 3, by adhering the electrode material peeling film 2 to both sides of the active material layer 12 of the electrode material 1, the active material layers 12 on both sides can be peeled off and collected in the recovery container 37.
[0027] According to the peeling method of the present invention, the active material layer can be peeled from the metal layer, regardless of whether it is a positive electrode material or a negative electrode material.
[0028] Furthermore, the peeling method of the present invention prevents metal foils such as aluminum, which are generated during the electrode material separation process from the current collector using conventional methods such as electric pulse methods, from being mixed into the recovered active material. Moreover, since the processing apparatus itself is relatively simple, it consumes little power, is highly safe, and is cost-effective.
[0029] The dry film thickness of the hot-melt adhesive layer is preferably 0.5 μm or more and 10 μm or less. The cured film thickness of the adhesive layer is preferably 0.5 μm or more from the viewpoint of adhesion. Furthermore, the cured film thickness of the adhesive layer is preferably 10 μm or less from the viewpoint of peelability.
[0030] Furthermore, the transmittance of the electrode material release film at a wavelength of 365 nm is preferably 85% or higher. By setting the transmittance to 85% or higher, sufficient ultraviolet irradiation is achieved to the UV-curable, easily release adhesive layer, and the adhesive effect is fully realized. As a result, peeling at the interface between the metal layer and the active material layer is improved.
[0031] The softening point of the hot-melt adhesive layer is preferably between 80°C and 155°C. From the viewpoint of adhesion to the active material layer 12, a softening point of 80°C or higher is preferable. Furthermore, from the viewpoint of energy consumption required for bonding, a softening point of 155°C or lower is preferable.
[0032] The thickness of the base film is preferably 10 μm or more and 300 μm or less. From the viewpoint of preventing film breakage during peeling, the thickness of the base film is preferably 10 μm or more. Furthermore, from the viewpoint of preventing peeling defects, the thickness of the base film is preferably 300 μm or less. [Examples]
[0033] The following describes in detail, with reference to an embodiment of the present invention, a film for peeling off electrode materials, and a peeling method using the film. However, the present invention is not limited to these embodiments.
[0034] [Extraction of positive electrode material] A commercially available lithium iron phosphate battery was disassembled, and the positive electrode material, consisting of lithium iron phosphate, a binder, and a conductive additive, and aluminum foil, was extracted. [Examples]
[0035] [Preparation of electrode material release film 2] A polyester-based hot-melt adhesive (PES-120L, manufactured by Toagosei Co., Ltd., R&D softening point: 125℃), dissolved in a toluene and MEK mixed solvent, was applied to an ultraviolet-curing, easily peelable adhesive film (Somatack UV125UV-C (thickness: 125μm), manufactured by Somar Co., Ltd.) using a bar coater to achieve a dry film thickness of 0.5μm. The film was then dried in air at 100℃ for 12 hours to form a film, thereby producing electrode material release film 2.
[0036] [Bonding with positive electrode material 1 and peeling off active material layer 12] The positive electrode material 1 was bonded to the hot-melt adhesive layer 22 of the electrode material release film 2 prepared as described above, so that the active material layer 12 was in contact with it. The bonding was then performed using a roll-heated transfer device (Navitas RT-150D) at a roll temperature of 200°C, taking care not to trap any air. After bonding, the positive electrode material 1 and the electrode material release film 2 were peeled off using the contact area with the transfer roll 32 as a starting point, thereby transferring the active material layer 12 to the electrode material release film 2 side.
[0037] The electrode material release film 2 on which the active material layer 12 has been transferred is irradiated with ultraviolet (UV) light from the base film 21 side (wavelength: 365 nm, irradiation dose: 500 mJ / cm²). 2 The following steps were taken. The electrode material release film 2 was then further transported by the transport roll 34 and the winding roll 35, and the active material layer 12 was separated from the electrode material release film 2 together with the hot-melt adhesive layer 22 by the separation roll 33 and the scraper 36. Specifically, it was separated into 1) a portion consisting of the active material layer 12 and the hot-melt adhesive layer 22, and 2) a portion consisting of the ultraviolet-curable easy-peel adhesive layer 20 and the base film 21. The separated portion consisting of the active material layer 12 and the hot-melt adhesive layer 22 was collected in the recovery container 37.
[0038] [Treatment of the active material layer 12] The active material layer 12 separated from the electrode material release film 2 was heated at 400°C to incinerate the hot-melt adhesive and the binder contained in the active material layer, thereby obtaining lithium iron phosphate powder.
[0039] [Battery evaluation] Using the lithium iron phosphate obtained by the above procedure, a coin cell was fabricated and evaluated (charge / discharge capacity). [Examples]
[0040] [Preparation of electrode material release film 2] A polyester-based hot-melt adhesive (PES-120L, manufactured by Toagosei Co., Ltd., R&D softening point: 125℃), dissolved in a toluene and MEK mixed solvent, was applied to an ultraviolet-curing, easily peelable adhesive film (Somatack UV125UV-C (thickness: 125μm), manufactured by Somar Co., Ltd.) using a bar coater to a dry film thickness of 10μm. The film was then dried in air at 100℃ for 12 hours to produce a film for releasing electrode materials. The subsequent operations were carried out in the same manner as in Example 1. [Examples]
[0041] [Preparation of electrode material release film 2] A polyester-based hot-melt adhesive (PES-140H, manufactured by Toagosei Co., Ltd., R&D softening point: 153°C), dissolved in a toluene and MEK mixed solvent, was applied to an ultraviolet-curing, easily peelable adhesive film (Somatack UV125UV-C (thickness: 125 μm), manufactured by Somar Co., Ltd.) using a bar coater to achieve a dry film thickness of 3 μm. The film was then dried in air at 100°C for 12 hours to produce a film for electrode material release. The subsequent operations were carried out in the same manner as in Example 1. [Examples]
[0042] [Preparation of electrode material release film 2] A film for electrode material release was prepared by applying an ethylene vinyl acetate (EVA)-based hot melt adhesive (WW528, manufactured by Toagosei Co., Ltd., R&D softening point: 83°C), dissolved in a toluene and MEK mixed solvent, to a UV-curing, easily peelable adhesive film (Somatack UV125UV-C (thickness: 125 μm), Somar Co., Ltd.) using a bar coater to a dry film thickness of 3 μm, and then drying it in air at 100°C for 12 hours. The following operations were carried out in the same manner as in Example 1. [Examples]
[0043] [Preparation of electrode material release film 2] A polyester-based hot-melt adhesive (PES-140H, manufactured by Toagosei Co., Ltd., R&D softening point: 153°C), dissolved in a toluene and MEK mixed solvent, was applied using a bar coater to a dry film thickness of 3 μm onto an ultraviolet-curing, easily peelable adhesive film (Prosave UV (thickness: 25 μm), manufactured by Kimoto Co., Ltd.). The film was then dried in air at 100°C for 12 hours to produce a film for electrode material release. The following operations were carried out in the same manner as in Example 1. [Examples]
[0044] [Preparation of electrode material release film 2] A polyester-based hot-melt adhesive (PES-120L, manufactured by Toagosei Co., Ltd., R&D softening point: 125℃), dissolved in a toluene and MEK mixed solvent, was applied by bar coating to a dry film thickness of 0.3μm onto an ultraviolet-curing, easily peelable adhesive film (Somatack UV125UV-C (thickness: 125μm), manufactured by Somar Co., Ltd.). The film was then dried in air at 100℃ for 12 hours to produce a film for electrode material release. The following operations were carried out in the same manner as in Example 1. [Examples]
[0045] [Preparation of electrode material release film 2] A polyester-based hot-melt adhesive (PES-120L, manufactured by Toagosei Co., Ltd., R&D softening point: 125℃), dissolved in a toluene and MEK mixed solvent, was applied to an ultraviolet-curing, easily peelable adhesive film (Somatack UV125UV-C (thickness: 125μm), manufactured by Somar Co., Ltd.) using a bar coater to a dry film thickness of 12μm. The film was then dried in air at 100℃ for 12 hours to produce a film for electrode material release. The following operations were carried out in the same manner as in Example 1.
[0046] The evaluation results for Examples 1 to 7 are shown in Table 1 below.
[0047] [Table 1]
[0048] In all of the electrode material release films in Examples 1 to 5, it was confirmed that they exhibited good release properties when the active material layer of the positive electrode material was peeled off and transferred to the electrode material release film side. In Examples 6 and 7, when transferring the active material layer of the positive electrode material to the electrode material release film, some residue of the active material layer remained on the positive electrode material side. However, it was confirmed that this level was not a practical problem. The evaluation (charge / discharge capacity) of coin cells made from lithium iron phosphate recovered using the electrode material peeling films of Examples 1 to 7 confirmed that all values were sufficient. [Explanation of Symbols]
[0049] 1 Electrode material 2. Film for releasing electrode material 11. Metal layer (aluminum foil) 12 Active material layer 20. Stimulant (UV) curing type easy-peel adhesive layer 21 Base film 22 Hot melt adhesive layer 30 Peeling device 31 Heating Roll 32 Transfer Rolls 33 Separation Roll 34 Conveyor Rolls 35 reel rolls 36 Scrapers 37 Collection containers
Claims
1. A film for releasing electrode materials, characterized by comprising a stimulus-curing, easily peelable adhesive layer on the surface of a base film, and a hot-melt adhesive layer provided on the stimulus-curing, easily peelable adhesive layer.
2. The electrode material peeling film according to claim 1, characterized in that the stimulus-curing type easily peelable adhesive layer is an ultraviolet-curing type easily peelable adhesive layer.
3. The electrode material release film according to claim 1, characterized in that the dry film thickness of the hot-melt adhesive layer is 0.5 μm or more and 10 μm or less.
4. The electrode material release film according to claim 2, characterized in that the transmittance of ultraviolet irradiation at a wavelength of 365 nm is 85% or more.
5. The electrode material release film according to claim 1, characterized in that the softening point of the hot-melt adhesive layer is 80°C or higher and 155°C or lower.
6. The electrode material release film according to claim 1, characterized in that the thickness of the base film is 10 μm or more and 300 μm or less.
7. The electrode material release film according to claim 1, characterized in that the electrode material is a positive electrode material.
8. The electrode material release film according to claim 1, characterized in that the electrode material is a negative electrode material.
9. A method for peeling an electrode material using an electrode material peeling film according to any one of claims 1 to 8, A step of bonding the hot-melt adhesive layer to the surface of the active material layer of an electrode material comprising a metal layer and an active material layer, A step of heating the hot-melt adhesive layer to bond the active material layer and the hot-melt adhesive layer, A step of peeling the active material layer from the metal layer using a transfer means and transferring the active material layer to an electrode material peeling film, A step of stimulating the electrode material peeling film to cure the stimulation-curing type easily peelable adhesive layer, A method for peeling off an electrode material, characterized by comprising a step of separating the active material layer from the electrode material peeling film using a separation means.
Citation Information
Patent Citations
Storage battery recycling method
JP2023086494A